Upgrading social e upgrading ambiental em cadeias globais de valor - Navarrete, Sabrina Della Santa (2019)
Participation in global value chains is considered critical for companies in emerging countries to gain access to the international market and opportunities in developed countries. In a scenario where production and service delivery processes are increasingly fragmented, the concepts of governance and upgrading determine the hierarchy among chain participants and the move towards higher value-added activities. Given the objective of analyzing the different types of upgrading still little explored in the literature, the research question that guided this work was the insertion in global value chains promotes social upgrading and environmental upgrading? Given the general objective of verifying if there is social and environmental upgrading in global value chains, this dissertation was structured in three independent but complementary articles to achieve the general objective of the research. In the first article, a systematic review of the Latin American literature was carried out, identifying the social dimensions that were compared through the optimistic and pessimistic view of the world scenario in contrast to the Latin American scenario. In the second article, through a systematic literature review, we sought to verify whether insertion into global value chains favors environmental upgrading at the country and sector level based on the United Nations environment-related Sustainable Development Goals (SDG). In the third, a quantitative approach was used through the structural equation modeling technique and multigroup analysis. Primary data resulting from survey research with respondents from India, Brazil, USA and Germany were used. We sought to verify whether economic upgrading is positively related to social upgrading and environmental upgrading, and whether the association between economic upgrading and social and environmental upgrading is stronger in developed countries than in emerging countries. The result obtained in the first article indicates a pessimistic view of integration, as in addition to not promoting social upgrading in some cases the participation of emerging countries in global value chains has made even worse a situation that was no longer ideal since the demands forced companies to adopt non-virtuous conduct. The consolidated result of the second article indicates an unfavorable outlook for environmental upgrading. The results of the third article revealed a positive association between economic upgrading and social upgrading as well as between economic upgrading and environmental upgrading. The results also indicated that although emerging countries are doing more upgrading in isolation, the association between economic upgrading and social upgrading, as well as economic upgrading and environmental upgrading is still stronger in developed countries.